Gold mining and social accountability: An empirical approach in Colombia - Saldarriaga-Isaza, Adrián; Florez-Herrera, Fernando; Ibáñez-Diaz, Marcela (Elsevier, 2025)
This paper aims to understand the impact of potential gold mining on social accountability. By using the Mediation Analysis method, we have developed an impact evaluation for a region of Colombia, through an empirical strategy that allows for the comparison of municipalities with and without potential gold mining. Our model's estimation considered two set of indicators: social accountability and social capital, which underwent Principal Component Analysis. We found that potential gold mining has a positive effect on social accountability, meaning that in municipalities with gold mining potential there is a greater use of participation tools, surveillance and control mechanisms by the local community. This effect is mediated by social capital, i.e., social capital causes the population of gold mining municipalities to implement social accountability. Some policy recommendations and conclusions are presented below.